The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fimmu.2022.1011166
|View full text |Cite|
|
Sign up to set email alerts
|

Malnutrition leads to increased inflammation and expression of tuberculosis risk signatures in recently exposed household contacts of pulmonary tuberculosis

Abstract: BackgroundMost individuals exposed to Mycobacterium tuberculosis (Mtb) develop latent tuberculosis infection (LTBI) and remain at risk for progressing to active tuberculosis disease (TB). Malnutrition is an important risk factor driving progression from LTBI to TB. However, the performance of blood-based TB risk signatures in malnourished individuals with LTBI remains unexplored. The aim of this study was to determine if malnourished and control individuals had differences in gene expression, immune pathways a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 65 publications
1
10
0
Order By: Relevance
“…TB is typically more prevalent in the undernourished population. 40 , 41 Our findings are thus consistent with these reports.…”
Section: Discussionsupporting
confidence: 93%
“…TB is typically more prevalent in the undernourished population. 40 , 41 Our findings are thus consistent with these reports.…”
Section: Discussionsupporting
confidence: 93%
“…Awareness of nutrition, balanced diet and regular physical activity should be improved by counselling and communication. "The authors declare no conflict of interest regarding this article" "The authors declare that all the procedures and experiments of this study respect the ethical standards in the Helsinki Declaration of 1975, as revised in 2008 (5), as well as the national law. Informed consent was obtained from all the patients included in the study".…”
Section: Discussionmentioning
confidence: 99%
“…Nutritional status is one of the most important determinants of resistance to infection, including TB. The interaction between TB and malnutrition has been well-established in the literature [3][4][5][6] . Undernutrition causes approximately 1/4 of all new TB cases worldwide and TB is one of the most frequent underlying causes of wasting 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have found that malnutrition plays an important role in the prognosis of many diseases, including infectious diseases, in ammation, and cancers. A lack of nutrition increased the susceptibility to infection, as well as reducing the quality and durability of vaccine responses 2 . An Indian study about nutritional status and pulmonary tuberculosis shown 85% patients with undernutrition had increased risk of death 3 .…”
Section: Introductionmentioning
confidence: 99%